(untitled) (Journal of Medical Sciences, 2021)
In Libya, using of insecticides is not well controlled compared to the developed countries. Therefore, the designed experiment was undertaken to identify the degree of damage caused by cypermethrin (CYP) on broiler cardio-skeletal muscles and to find out safety dose that may minimize toxic residues in chicken meat. 4 groups of broiler (10 each) were administrated water without (control) or mixed with CYP ( 7mg, 14mgand 21mgbody weight) for 2 weeks. After completion experiment period, heart and skeletal muscle samples were taken from breast, thigh and leg, using standard procedure and fixed in 10% buffered formalin saline, followed by immersion the tissues in a series of gradually increasing concentration of alcohol and xylene, then embedded in hard paraffin and sectioned at 3 um. Special stains were used to study histological alternations and examined under light microscope. The gross observations showed pathological changes on heart, whereas no lesions found in skeletal samples. CYP intoxicated broiler chickens showed loss normal architectures of cardio-skeletal myocytes represented in wide intercellular spaces, high amount of collagen and elastic fibers, adipose tissue found between muscle fibers, congested blood vessels and extravasation of blood cells observed in an inter-ventricular septum of cardiac tissue. Histochemical investigations revealed increase glycogen deposition between and within cardio-skeletal myocytes. The study concluded that CYP promote histological alternations in broiler cardio-skeletal myocytes even at low concentration.